(untitled) (Proceedings of International Conference on Special Education, 2015)
Technology-aided instruction and intervention (TAII) is an evidence-based practice intervention method for autistic individuals. With three-dimensional display and body awareness, somatic games are video games operated through body movements. It achieves human-computer interaction in an effective way, and has great potential to support autistic individuals to obtain target skills. This study reviews research literature on the studies of intervention in autistic children by using somatic games, sums up the strength and problems of the study, and then gives enlightenment on related research and practice in future.